Defining parameters of specificity for bioluminescent optogenetic activation of neurons using in vitro multi electrode arrays (MEA). Issue 3 (28th August 2018) - Prakash, Mansi; Medendorp, William E.; Hochgeschwender, Ute
Abstract: In Bioluminescent Optogenetics (BL‐OG) a biological, rather than a physical, light source is used to activate light‐sensing opsins, such as channelrhodopsins or pumps. This is commonly achieved by utilizing a luminopsin (LMO), a fusion protein of a light‐emitting luciferase tethered to a light‐sensing opsin. Light of the wavelength matching the activation peak of the opsin is emitted by the luciferase upon application of its small molecule luciferin, resulting in activation of the fused opsin and subsequent effects on membrane potential. Using optimized protocols for culturing, transforming, and testing primary neurons in multi electrode arrays, we systematically defined parameters under which changes in neuronal activity are specific to bioluminescent activation of opsins, rather than due to off‐target effects of either the luciferin or its solvent on neurons directly, or on opsins directly. We further tested if there is a direct effect of bioluminescence on neurons. Critical for assuring specific BL‐OG effects are testing the concentration and formulation of the luciferin against proper controls, including testing effects of vehicle on LMO expressing and of luciferin on nonLMO expressing targets. Abstract : In Bioluminescent Optogenetics (BL‐OG) a luciferase acts on its luciferin, CTZ, thereby emitting light which activates the fused optogenetic element. By systematically probing effects of CTZ and solvent through in vitro multi electrode recordings from untransduced neurons and from neurons expressing the opsin alone, the luciferase alone, or the luciferase‐opsin fusion protein (luminopsin) we defined parameters under which changes in neuronal activity are specific to BL‐OG.